Faculty cooperation in teaching academic literacy using popular science texts: A case study - Wu, Siew Mei; Lee, Sze Han; Chan, Eric Chun Yong (Teaching and Learning Inquiry, 2018)
Developing strong communicative ability amongst science graduates, especially in science communication, has been included as a fundamental learning outcome in some science degree programmes. This article focuses on a compulsory academic literacy course for first-level undergraduates that is aimed at developing academic reading and writing skills beyond the considerations of deficit language proficiency. It straddles the general, discipline-specific dichotomy in the skills aimed at, course content, and materials used. It targets two core science communication skills in addition to general academic literacy. In addition, the content and materials consist of popular science and media texts to facilitate the discussion of scientific ideas made accessible to the lay reader. It investigates course effectiveness on developing coherence in students’ writing. Results obtained suggest that indicators of coherence, especially in the integration of source ideas and writers’ proposition and the logical progression of textual ideas, are correlated to the difference in improved essay scores.